Data of all figures - Bingqing Ye (5149703) (2025)
Sepsis, a life-threatening organ dysfunction caused by dysregulated host responses to infection, often leads to sepsis-associated acute lung injury (SALI), a major contributor to mortality. Spermidine (SPD), a natural polyamine with anti-inflammatory and metabolic regulatory properties, has emerged as a potential nutritional adjunct for sepsis management. However, whether and how SPD ameliorates SALI remains to be elucidated. Here, cecal ligation and puncture (CLP) was performed in rats to simulate sepsis. Rat survival, lung injury score, Dry/Wet ratio, histopathology, cytokine levels and immunohistochemical analysis were analyzed to evaluate SPD’s effects on SALI. Targeted metabolomics, molecular docking and cellular thermal shift assay (CETSA) identified AMP-activated protein kinase (AMPK) as an underlying target of SPD’s action. In vitro investigations were based on lipopolysaccharide (LPS)-stimulated bone marrow-derived macrophages (BMDMs), with flow cytometry assessing apoptosis. AMPK inhibitor (Compound C) and downstream signaling were examined in vivo and in vitro through q-PCR and Western blot experiments. Consequently, SPD improved rat survival, reduced lung injury, and decreased pro-inflammatory cytokines in CLP rats. Metabolomics, molecular docking and CETSA suggested AMPK-mediated energy metabolism modulation. Mechanistically, SPD attenuated necroptosis via AMPK/RIPK1/MLKL signaling. Moreover, Compound C counteracted the protective effect of SPD on SALI in vivo and in vitro. Our findings evidence that SPD significantly ameliorates SALI via the regulation of AMPK-mediated necroptosis. SPD supplementation may serve as a complementary therapeutic approach, warranting further investigation in subsequent clinical trials for sepsis treatment.